Genetic predisposition to hypertension is associated with preeclampsia in European and Central Asian women - Valgerdur Steinthorsdottir (Nature Portfolio, 2020)
Studies to identify maternal variants associated with preeclampsia have been limited by sample size. Here, the authors meta-analyze eight GWAS of 9,515 preeclamptic women, identifying five variants associated with preeclampsia and showing that genetic predisposition to hypertension is a major risk factor for preeclampsia.